2015
DOI: 10.1128/jvi.02472-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues in the Human Respiratory Syncytial Virus Fusion Protein That Modulate Fusion Activity and Pathogenesis

Abstract: Human respiratory syncytial virus (RSV) lower respiratory tract infection can result in inflammation and mucus plugging of airways. RSV strain A2-line19F induces relatively high viral load and mucus in mice. The line 19 fusion (F) protein harbors five unique residues compared to the non-mucus-inducing strains A2 and Long, at positions 79, 191, 357, 371, and 557. We hypothesized that differential fusion activity is a determinant of pathogenesis. In a cell-cell fusion assay, line 19 F was more fusogenic than Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…A dual-split-protein (DSP) cell-to-cell fusion assay was used to quantify fusion activity of expressed RSV F proteins as described previously (23)(24)(25). The consensus BAF gene was obtained in mammalian codon optimized form from GeneArt and cloned into pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…A dual-split-protein (DSP) cell-to-cell fusion assay was used to quantify fusion activity of expressed RSV F proteins as described previously (23)(24)(25). The consensus BAF gene was obtained in mammalian codon optimized form from GeneArt and cloned into pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…In viral infections affecting the upper or lower respiratory tracts, such as influenza viruses and respiratory syncytial virus (RSV), the increased production of mucus, which is largely composed of mucins, is commonly induced in the epithelial surfaces of the respiratory tract (11,12). Recent studies have revealed that mucins are upregulated in epithelial cells soon after infection by respiratory viruses, such as influenza A virus (IAV), both in vivo and in vitro.…”
mentioning
confidence: 99%
“…This raises the interesting question of the tolerance of fusion protein mutations in the context of infectious virus, especially in relation to our fusion-increasing mutations. This study and others have seen the fusogenicity of transfected F mutations mimic the same phenotype when they are part of an infectious virus (32,33). Even though many of our mutations show an increase in the fusion phenotype, the amino acid sequence of HRC is genetically stable, suggesting that the area does not tolerate change.…”
Section: Discussionmentioning
confidence: 96%
“…However, circulating virus is faced with the challenge of withholding transition until an appropriate host cell membrane is available. Correlation has been found between an increase in fusion activity and higher viral load and pathogenesis in mice for both RSV (33) and other paramyxoviruses (34). Thus, circulating virus faces competing selective pressures of balancing the infectious half-life of transmitted virions and fusion capacity.…”
Section: Discussionmentioning
confidence: 99%